Biodiversity and host-parasite cophylogeny of Sphaerospora (sensu stricto) (Cnidaria: Myxozoa) - Patra, Sneha; Bartošová-Sojková, Pavla; Pecková, Hana; Fiala, Ivan; Eszterbauer, Edit; Holzer, Astrid S (Parasites & vectors, 2018)
BACKGROUND: Myxozoa are extremely diverse microscopic parasites belonging to the Cnidaria. Their life-cycles alternate between vertebrate and invertebrate hosts, predominantly in aquatic habitats. Members of the phylogenetically well-defined Sphaerospora (sensu stricto) clade predominantly infect the urinary system of marine and freshwater fishes and amphibians. Sphaerosporids are extraordinary due to their extremely long and unique insertions in the variable regions of their 18S and 28S rDNA genes and due to the formation of motile proliferative stages in the hosts' blood. To date, DNA sequences of only 19 species have been obtained and information on the patterns responsible for their phylogenetic clustering is limited. METHODS: We screened 549 fish kidney samples from fish of various geographical locations, mainly in central Europe, to investigate sphaerosporid biodiversity microscopically and by 18S rDNA sequences. We performed multiple phylogenetic analyses to explore phylogenetic relationships and evolutionary trends within the Sphaerospora (s.s.) clade, by matching host and habitat features to the resultant 18S rDNA trees. The apparent co-clustering of species from related fish hosts inspired us to further investigate host-parasite co-diversification, using tree-based (CoRE-PA) and distance-based (ParaFit) methods. RESULTS: Our study considerably increased the number of 18S rDNA sequence data for Sphaerospora (s.s.) by sequencing 17 new taxa. Eight new species are described and one species (Sphaerospora diminuta Li & Desser, 1985) is redescribed, accompanied by sufficient morphological data. Phylogenetic analyses showed that sphaerosporids cluster according to their vertebrate host order and habitat, but not according to geography. Cophylogenetic analyses revealed a significant congruence between the phylogenetic trees of sphaerosporids and of their vertebrate hosts and identified Cypriniformes as a host group of multiple parasite lineages and with high parasite diversity. CONCLUSIONS: This study significantly contributed to our knowledge of the biodiversity and evolutionary history of the members of the Sphaerospora (s.s.) clade. The presence of two separate phylogenetic lineages likely indicates independent historical host entries, and the remarkable overlap of the larger clade with vertebrate phylogeny suggests important coevolutionary adaptations. Hyperdiversification of sphaerosporids in cypriniform hosts, which have undergone considerable radiations themselves, points to host-driven diversification.
Keywords: parazitární nemoci u zvířat; biologická evoluce; Taxonomy; Teleost; biodiverzita; Sphaerospora sensu stricto; Host-parasite codiversification; Biological Evolution; DNA, Ribosomal; Myxozoa; zvířata; nemoci ryb; fylogeneze; ribozomální DNA; Cnidaria; Biodiversity; Parasitic Diseases, Animal; Fish Diseases; Fishes; ryby; Phylogeny; Animals